2020
DOI: 10.3389/fpsyg.2019.03092
|View full text |Cite
|
Sign up to set email alerts
|

Viewing Landscapes Is More Stimulating Than Scrambled Images After a Stressor: A Cross-disciplinary Approach

Abstract: Research has demonstrated that nature is beneficial for many aspects of one's health. This pilot study aimed to investigate whether viewing landscape artworks, as a form of representational nature, could improve psychological and physiological recovery from a laboratory stressor. A sample of 30 participants was randomized to one of two conditions: landscape and scrambled. After a laboratory stress task, participants in the landscape condition viewed a series of landscape paintings for 30 min; participants in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 42 publications
4
12
0
Order By: Relevance
“…Our results are generally supported by a recent study, which revealed beneficial effects by viewing landscape art, but not for their respective phase-scrambled versions (Law et al, 2020). This study did, however, not include a control environment (i.e., paintings of urban scenes), so that one cannot disentangle whether their observed effects come from the possibility to recognize any objects, from recognizing the image as art, and/or from recognizing the scene as nature.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our results are generally supported by a recent study, which revealed beneficial effects by viewing landscape art, but not for their respective phase-scrambled versions (Law et al, 2020). This study did, however, not include a control environment (i.e., paintings of urban scenes), so that one cannot disentangle whether their observed effects come from the possibility to recognize any objects, from recognizing the image as art, and/or from recognizing the scene as nature.…”
Section: Discussionsupporting
confidence: 86%
“…Despite the discussed inconsistencies to previous findings and the possibility of false negative findings, we believe that the current null results suggest that the lack of spatial information and/or certain other image characteristics (e.g., edge properties) diminishes pronounced perceived restoration effects, and that the amplitude spectrum and colour properties seem to play no or rather minor roles for restoration. A similar finding using landscape paintings and their phase-scrambled counterparts was published recently (Law et al, 2020) Overall the results indicate that the spatial information available in original images and line drawings, which allowed higher-order processing (i.e., recognizing objects and the environment), seems to evoke perceived restoration and higher liking ratings for nature compared to urban environments. However, so far one cannot conclude whether these effects were solely due to the recognition of the environment and the respective associations or were also influenced by differing edge-related image properties since line drawings of nature and urban environments still vary systematically in some properties (S3 in the Supplemental Material).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Law et al 25 Conducted a pilot study to investigate whether nature artworks could improve recovery from a laboratory stressor. Participants were randomised to either view a 30 min digital slideshow of landscape artworks or digitally scrambled versions of these artworks after being exposed to a laboratory stressor.…”
Section: Key Findingsmentioning
confidence: 99%
“…23 Nature content may also affect biological indicators of stress responses; cortisol levels decreased faster after a stressor in people viewing scrambled versions of nature artworks, compared with the original nature artworks. 25 The remaining two studies 9 20 did not report on the content of the artwork, and therefore, cannot be categorised.…”
Section: Content Of Artworkmentioning
confidence: 99%